Determinants of Mother-To-Child Transmission of HIV Infection in Rachuonyo East Subcounty, Homabay County, Kenya - Ogone, Nicholas Odiemo (Jooust, 2022)
Vertical transmission is the commonest mode of Human Immunodeficiency Virus (HIV) infection in children aged below 5 years. It remains one of the HIV pandemic’s most important challenges. Without preventive measures, chances of the unborn child acquiring HIV in the uterus or during delivery are 15-30%, increasing to 20-45% with breastfeeding. Preventionof mother-to-child transmission (MTCT) strategies can reduce HIV infections to below 1% in developed countries though little success is being realized in developing countries.This study investigated factors influencing MTCT of HIV among children under 5 years in Rachuonyo East Sub County, Homabay County, Kenya. A cross sectional study was conducted in Rachuonyo East Sub County between November 2020 and April 2022. A validated semi structured questionnaire was used to obtain data from 120 randomly sampled HIV positive mothers paired with their children. Data analysis was performed using Chi square tests, Fishers Exact tests and binary logistic regression. The study showed that HIV positive mothers’ pregnancy willingness was significantly associated with prevention of MTCT of HIV. Women who were willing to get pregnant were 49.7 times more likely to achieve prevention of MTCT of HIV compared to those who were unwilling (AOR=49.71; 95% CI 2.20-1125.54). Themean age of the participants was 27.8 (SD = 6.4). There was significant association between number of live births and prevention of MTCT of HIV ( p <0.05). In addition, women with at least four MTCT visits during pregnancy were 8.6 times more likely to achieve prevention of MTCT of HIV than those who had less than four visits (AOR=8.60; 95% CI 0.45-163.72). Women who never migrated from health care facilities initially enrolled in for HIV care and treatment were 34.4 times more likely to achieve prevention of MTCT of HIV as compared to those who ever migrated (AOR = 34.47; 95% CI 4.84-245.34).Majority of the women 78 (65.0%) possessed above average knowledge on when mother to child transmission of HIV can occur. Women who had average knowledge (AOR = 5.83; 95% CI 0.29-118.26) and excellent knowledge (AOR = 5.62; 95% CI 0.23-138.25) of MTCT during pregnancy were 5.6 and 5.8 times respectively more likely to achieve prevention of mother-to-child transmission of HIV than those who had below average knowledge. Pregnancy willingness and migration between health facilities predicted MTCT in this study area. Social support to HIV infected mothers, policy adjustments regarding transfer of patients on HIV care between health facilities and intensive health messaging are key to achieving MTCT.
Keywords: HIV Infection.; Mother-To-Child Transmission of HIV Infection, Kenya.